2021
DOI: 10.1126/science.abh4054
|View full text |Cite
|
Sign up to set email alerts
|

Florigen sequestration in cellular membranes modulates temperature-responsive flowering

Abstract: Linking flowering to ambient temperature In the small mustard plant Arabidopsis , the florigen FLOWERING LOCUS T (FT) mobilizes to initiate flowering at the shoot apical meristem. Susila et al . now show that FT, which is produced in leaf cells, can be held in reserve if ambient temperatures are not favorable (see the Perspective by Jaillais and Parcy). At low temperatures, FT binds a membrane phosopholipid and is thus restricted in mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 64 publications
3
52
0
2
Order By: Relevance
“…Flowering/heading time is a key agronomic trait that determines cropping season and regional adaptability [ 35 ], hence an important agricultural trait for crop (such as rice) breeding. Lipid-mediated signaling has been shown to play crucial roles in regulating flowering time [ 26 , 28 ]. By combining functional genomics and systemic phospholipids profile analysis, our studies suggested that a secretory spPLD suppresses rice heading date through decreasing the content of light period predominant PC species, which leads to the reduced activity of primary pump (H + -ATPase) at plasma membrane and less driving force for Hd3a/RFT1 entering cell, hence the decreased Hd3a/RFT1 activity and delayed heading ( Fig 5D ), revealing the importance of a secretory spPLD in the lipid-mediated regulation of heading time in rice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flowering/heading time is a key agronomic trait that determines cropping season and regional adaptability [ 35 ], hence an important agricultural trait for crop (such as rice) breeding. Lipid-mediated signaling has been shown to play crucial roles in regulating flowering time [ 26 , 28 ]. By combining functional genomics and systemic phospholipids profile analysis, our studies suggested that a secretory spPLD suppresses rice heading date through decreasing the content of light period predominant PC species, which leads to the reduced activity of primary pump (H + -ATPase) at plasma membrane and less driving force for Hd3a/RFT1 entering cell, hence the decreased Hd3a/RFT1 activity and delayed heading ( Fig 5D ), revealing the importance of a secretory spPLD in the lipid-mediated regulation of heading time in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endosomal trafficking is involved in FT movement and transport [ 49 ] and various phospholipids including PA and PI(4,5)P 2 regulate the endosomal trafficking of target proteins through binding or regulating vesicle trafficking [ 4 , 50 ]. Indeed, a recent study revealed that negatively charged phospholipid PG could bind FT and affect the FT movement to regulate the temperature-insensitive flowering [ 28 ], which suggests that FT-phospholipid binding specificity may differ depending on the distinct localization and function [ 51 ]. How various phospholipids regulate Hd3a/RFT1 activity and hence flowering under different developmental or environmental factors need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent breakthrough indicates that the negatively charged phospholipid PG (phosphatidyl-glycerol) on the cellular membranes of lipid bilayer can interact with the FT protein, and sequester FT [ 82 ]. Low temperature promotes FT sequestration in the cellular membrane of the CC, thereby reducing the level of soluble FT and delaying the transition to flowering [ 82 ]. These findings reveal the mechanism underlying how plants modulate the activity of florigen to optimize the timing of flowering in response to temperature changes.…”
Section: Molecular Mechanisms For the Photoperiodic Regulation Of Flowering In Arabidopsismentioning
confidence: 99%
“…PHOSPORYLETHANOLAMINE CYTIDYLTRANSFERASE1 (PECT1) modulates the ratio of phosphatidylethanolamine:ph osphatidylcholine (Mizoi et al, 2006). The artificial microRNAmediated knockdown of PECT1 in the SAM (pFD::amiR-PECT1) resulted in reduced SVP mRNA levels and consequent upregulation of GA20ox2 in the SAM, leading to early flowering independent of the photoperiod (Susila et al, 2021a). These findings showed the importance of GAs in promoting the floral transition in plants with altered ratios of structural phospholipids (including phosphatidylethanolamine and phosphatidylcholine) and the role of SVP, which provides a link between altered phospholipid ratios and GA biosynthesis.…”
Section: Gibberellinsmentioning
confidence: 99%